Farmers׳ perceptions of developing forest based bioenergy in China. (May 2016) - Qu, Mei; Lin, Ying; Liu, Can; Yao, Shunbo; Cao, Yang
Abstract: Farmers′ awareness of forest-based bioenergy developments will greatly determine the direction and succession of forestry projects. To obtain a better understanding of this awareness, a logistic regression model was applied to analyze the factors influencing farmers′ willingness to participate in the construction of bioenergy bases. The model was developed based on a survey of 573 household farmers in eight Chinese provinces. This study found that a majority of households have increased their daily use of commercial fuel. Moreover, a significant number of farmers are either uncertain about or unfamiliar with the concept of forest-based bioenergy. The model found that households with young and educated individuals, a higher forestland endowment, and a higher cognition and understanding of fossil fuels, have a higher willingness to learn about and participate in forest based bioenergy issues. The findings of this study will be useful for bioenergy forest cultivators, extension foresters, forest landowners, and policy makers.